In search of the Palaeogene-Neogene Boundary Stratotype (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
In publishing the first results of its research works (Giornale di Geologia, vol. XLIV, fasc. l-Il, 1981 ) the Palaeogene/Neogene Boundary Working Group, while not having defined any final object yet, has nonetheless enabled us to: a) recall attention to the existence of lithofacies (e. g. turbidites, volcanoclastic rocks) of great significance with respect to the geodynamical situation of the Mediterranean; b) to clarify the significance of some first class faunal markers, particularly as regards planktonic foraminfera.These results permitted to direct the course of subsequent research works carried out by the Group, m the way of giving to the International Commission on Stratigraphy. some objective data for a satisfactory solution of the problem.
Keywords: Palaeogene/Neogene; Oligocene/Miocene; lithostratlgraphy; biostratigraphy; chronostratigraphy; potential boundary stratotype section; Italy (Sicily); Spain (Betic Cordilleras); equatorial Pacific Ocean; planktonic foraminifera environments; paleoecology of micromammals.